Development of Intelligent Planning & Integrated Office Management System for Drilling Operations in South Azadagan. Issue 1 (April 2021) - Liu, Zhikun; Li, Aixi; Li, Jihui; Bai, Mingna
Abstract: Due to the distance limitation between the drilling department in Iran and the head office in China, it is necessary to improve the management level of the south Azadagan drilling department in the south of Iran. According to the drilling operation characteristics of Iran south Azadagan department, we design and develop an Intelligent Planning & Integrated Office Management System (IPIOMS) including design management, work report, planning and cost control, operation management, statistical query and logistics support.